2006
DOI: 10.1159/000093777
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster and Its Cardiovascular Complications in the Elderly – Another Look at a Dormant Virus

Abstract: Herpes zoster (shingles) is a reactivation of latent Varicella-zoster virus (VZV). We present a case of pleuropericarditis simulating acute myocardial infarction and another with complete heart block in the setting of acute/recent VZV reactivation. These cases are consistent with a modified concept: (1) the VZV dormancy is comprised of multiple foci of infections in the sensory and autonomic ganglia, and (2) the VZV reactivation could involve co-incident activations of two or more loci. Recognition of this pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Sporadic occurrences of chickenpox‐related cardiovascular events in children and young adults have been reported recently, including pericarditis [Nandeesh et al, ], myocarditis and myoepicarditis [De et al, ], cardiac tamponade, and pericardial effusion [Masood et al, ]. The cardiovascular complications of herpes zoster have also been reported as varicella zoster myoepicarditis in a previously healthy young man [Biocic et al, ], complete heart block in a 64‐year‐old white male [Ma et al, ] and myocardium infarction symptom that finally diagnosed as myocarditis in a 16‐year‐old male [Kelly et al, ]. However, there has been no population‐based epidemiology study on the association between varicella‐zoster virus and heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sporadic occurrences of chickenpox‐related cardiovascular events in children and young adults have been reported recently, including pericarditis [Nandeesh et al, ], myocarditis and myoepicarditis [De et al, ], cardiac tamponade, and pericardial effusion [Masood et al, ]. The cardiovascular complications of herpes zoster have also been reported as varicella zoster myoepicarditis in a previously healthy young man [Biocic et al, ], complete heart block in a 64‐year‐old white male [Ma et al, ] and myocardium infarction symptom that finally diagnosed as myocarditis in a 16‐year‐old male [Kelly et al, ]. However, there has been no population‐based epidemiology study on the association between varicella‐zoster virus and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation on the endothelium cells of vascular walls may lead to atherosclerosis and cause cardiovascular diseases. Several case studies have reported the vague association between herpes zoster and cardiovascular complications, including pleuropericarditis and complete heart block [Spillane and White, ; Cohen et al, ; Ma et al, ; Kelly et al, ; Masood et al, ; Biocic et al, ; Nandeesh et al, ; De et al, ]. However, no study has explored the association between these two disorders using population data.…”
Section: Introductionmentioning
confidence: 99%
“…Two reports describe cardiac arrhythmia associated with zoster. The first was a 64-year old man who developed right T8-distribution zoster followed 2 months later by complete heart block [3]. The second was a 34-year-old man who simulaneously developed ventricular fibrillation and disseminated zoster whose skin, throat and nose swabs contained VZV DNA [4].…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation of varicela zoster has also been recently described as cause of pleuroperdicaditis in an older patient [ 143 ] . Despite its rarity this entity needs to be considered in the differential diagnosis of patients with chest pain, especially in those of advanced age or immuno-compromised.…”
Section: Herpes Zostermentioning
confidence: 95%